Chronic pulmonary aspergillosis – chronic cavitary pulmonary aspergillosis: a case report - Francis Celeste; Ency Eveline (Intisari Sains Medis, 2020)
Background: Chronic pulmonary aspergillosis (CPA) includes several disease manifestations. Almost all cases of CPA are caused by A. fumigatus. There are several underlying diseases that predispose patients to CPA. Treatment is often individualised depending on underlying disease process and the patient’s pulmonary status.Case presentation: A 57-year-old male with a history of renal transplant in the year 2006, routine on immunosuppressants, pulmonary tuberculosis relapse on anti-tuberculosis medications, aspergillosis on long term voriconazole, and DM type 2 presented with dyspnea, massive hemoptysis and productive cough 3 months before admission. Patient was diagnosed with aspergillosis in October 2012 through bronchoscopy. Microbiology result showed Aspergillus flavus. Enhanced thoracal CT result showed a cavitating nodule with soft tissue lesion in upper right lung, with fibrotic changes in the right lung and mild tubular bronchiectasis, with bilateral pleural thickening. Patient was then planned for lung resection due to the persistent pulmonary cavity. However, his clinical condition worsened and the patient passed away a few days before surgery.Conclusion: Diagnosing chronic pulmonary aspergillosis can often be challenging. The diagnosis of CPA can be inferred from a single chest radiograph. Despite this, detailed and sequentially acquired radiographic data may be required to observe both the typical radiographic features and the very slow progression of this disease. Treatment is often individualised. Azoles are the antifungal drug of choice when required.